2000
DOI: 10.1210/jc.85.8.2805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Insulin-Like Growth Factor I Administration on Spontaneous and Growth Hormone (GH)-Releasing Hormone-Stimulated GH Secretion in Anorexia Nervosa

Abstract: Exaggerated GH and reduced insulin-like growth factor I (IGF-I) levels are common features in anorexia nervosa (AN). A reduction of the negative IGF-I feedback could account, in part, for GH hypersecretion. To ascertain this, we studied the effects of recombinant human (rh)IGF-I on spontaneous and GH-releasing hormone (GHRH)-stimulated GH secretion in nine women with AN [body mass index, 14.1 Ϯ 0.6 kg/m 2 ] and in weight matched controls (normal weight). Mean basal GH concentrations (mGHc) and GHRH (2.0 g/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
15
1
1
Order By: Relevance
“…Reportedly, GH secretion is increased in the florid phase of the disease, and, although this has been related to a loss of the feedback action of circulating IGF-I (Berelowitz et al 1981, Counts et al 1992, Ross & Chew 1995, Gianotti et al 2000, a primary hyperfunction of GHRH-secreting neurons cannot be disregarded (Scacchi et al 1997, Stoving et al 1999a, 1999b, Gianotti et al 2000, Pincelli et al 2002. If this were the case, one cannot rule out the possibility that GHRH-secreting neurons are, in turn, under an enhanced stimulation by hypothalamic ghrelin-secreting neurons (Hewson & Dickson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, GH secretion is increased in the florid phase of the disease, and, although this has been related to a loss of the feedback action of circulating IGF-I (Berelowitz et al 1981, Counts et al 1992, Ross & Chew 1995, Gianotti et al 2000, a primary hyperfunction of GHRH-secreting neurons cannot be disregarded (Scacchi et al 1997, Stoving et al 1999a, 1999b, Gianotti et al 2000, Pincelli et al 2002. If this were the case, one cannot rule out the possibility that GHRH-secreting neurons are, in turn, under an enhanced stimulation by hypothalamic ghrelin-secreting neurons (Hewson & Dickson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism could involve the reduced IGF-I levels produced by malnutrition. Gianotti et al (61) showed that a low IGF-I dose inhibits, though does not normalize, spontaneous and stimulated GH secretion in patients with AN. These findings indicate the existence of a defective hypothalamic control of GH release (61).…”
Section: Gh -Igf-i Axismentioning
confidence: 99%
“…Gianotti et al (61) showed that a low IGF-I dose inhibits, though does not normalize, spontaneous and stimulated GH secretion in patients with AN. These findings indicate the existence of a defective hypothalamic control of GH release (61). This would effect a reduction in the negative feedback action that IGF-I exerts on GH secretion at the level of both the hypothalamus and the pituitary (60).…”
Section: Gh -Igf-i Axismentioning
confidence: 99%
“…However, the GH-secretory response to reduced food intake is species dependent. In humans, nutrient deprivation results in a rise in circulating GH (Ho et al 1988, Riedel et al 1995, Stoving et al 1999 accompanied by a paradoxical decrease in insulin-like growth factor (IGF)-I due to the GH resistance of peripheral target tissues (Ho et al 1992, Gianotti et al 2000. The increase in GH release is associated with an increase in pituitary sensitivity to growth hormone-releasing hormone (GHRH) and a decrease in pituitary sensitivity to somatostatin (SRIF) (Gianotti et al 1999).…”
Section: Introductionmentioning
confidence: 99%